The intelligent REIT investor : how to build wealth with real estate trusts - Krewson-Kelly, Stephanie; Thomas, Brad, 1966- (John Wiley & Sons, Inc., 2016)
The go-to guide for smart REIT investing The Intelligent REIT Investor is the definitive guide to real estate investment trusts, providing a clear, concise resource for individual investors, financial planners, and analysts-anyone who prioritizes dividend income and risk management as major components to wealth-building. Later this year, the REIT industry will experience a watershed event when Standard & Poors creates a new Global Industry Classification Standard (GICS) sector called Real Estate. On September 1st, publicly traded equity REITs will be removed from Financials, where they have been classified since their creation in 1960, and begin trading as their own S & P Sector. This separation from banks and financial institutions already is attracting new investors, but REITs require an industry-specific knowledge that is neither intuitive or readily accessible to newcomers-until now. Using straightforward language and simple example to illustrate important concepts, this book will enable any reader to quickly learn and understand the lexicon and valuation techniques used in REIT investing, providing a wealth of practical resources that streamline the learning process. The discussion explains terminology, metrics, and other key points, while examples illustrate the calculations used to evaluate opportunities. A comprehensive list of publicly-traded REITs provides key reference, giving you access to an important resource most investors and stockbrokers lack. REITs are companies that own or finance commercial rental properties, such as malls and apartment buildings. Despite historically high total returns relative to other investments, such as the Nasdaq or S & P 500 index, most investors are unfamiliar with the REIT industry, and wary of investing without adequate background. This book gets you up to speed on the essentials of REIT investing so you can make more informed-and profitable-decisions.-Understand REITs processes, mechanisms, and industry -Calculate key metrics to identify suitable companies -Access historical performance tables and industry-specific terminology -Identify publicly-traded REITs quickly and easily REITs have consistently outperformed many more widely known investments. Over the past 15-year period, for example, REITs returned an average of 11% per year, better than all other asset classes. Since 2009, REITs have enjoyed positive returns; large cap stocks and cash are the only other classes that paralleled that record. Even in 2015, a 'year of fear' related to rising rates, REITs returned 2.4%, beating most all other asset classes. REITs have a long history (over fifty years) of performance, and are about to enter the big leagues. If you feel like you've been missing out, don't keep missing out. Prepare yourself, and your portfolio, to benefit from the demand for REITs that will follow the creation of a Real Estate GICS sector. The Intelligent REIT Investor gives you the information you need to invest wisely and manage your real estate risk effectively. By maintaining a tactical exposure in the brick and mortar asset class, investors should benefit from the information contained in The Intelligent REIT Investor. Join the REIT world and look forward to owning stocks that will help you to sleep well at night.